2014
DOI: 10.1016/j.abb.2014.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Canavalia ensiformis urease, Jaburetox and derived peptides form ion channels in planar lipid bilayers

Abstract: Ureases catalyze the hydrolysis of urea into NH3 and CO2. They are synthesized by plants, fungi and bacteria but not by animals. Ureases display biological activities unrelated to their enzymatic activity, i.e., platelet and neutrophil activation, fungus inhibition and insecticidal effect. Urease from Canavalia ensiformis (jack bean) is toxic to several hemipteran and coleopteran insects. Jaburetox is an insecticidal fragment derived from jack bean urease. Among other effects, Jaburetox has been shown to inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 61 publications
0
33
0
Order By: Relevance
“…The ability of these peptides to form ion channels in lipid bilayers was also confirmed by testing with planar lipid bilayers (PLB) [15]. In this study, it was shown that the peptide, as well as the above mentioned mutants can insert themselves into planar lipid bilayers and form cation selective ion channels.…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…The ability of these peptides to form ion channels in lipid bilayers was also confirmed by testing with planar lipid bilayers (PLB) [15]. In this study, it was shown that the peptide, as well as the above mentioned mutants can insert themselves into planar lipid bilayers and form cation selective ion channels.…”
Section: Introductionmentioning
confidence: 74%
“…Barros et al [38] observed that JBTX was able to permeabilize acidic liposomes to release entrapped carboxy-fluorescein. Piovesan et al [15] reported that JBTX, as well as some of its truncated mutants, was capable of inserting itself into neutral planar lipid bilayers forming cation-selective ion channels. More recently, Micheletto et al [39] studied by small angle X-ray scattering (SAXS) the interaction among JBTX and multilamellar liposomes with a lipid composition typical of human platelets membrane.…”
Section: Is There Any Effect On Membranes?mentioning
confidence: 99%
“…Considering the membrane-disturbing properties of Jaburetox [19,23,24], we would expect that the polypeptide would change its conformation to a folded state when in contact with membranes. The full assignment of Jaburetox reported here will allow us to perform NMR studies of this toxic polypeptide in contact with lipid micelles mimicking insect and fungus membranes [78], determining changes in its conformation properties based on modifications of the 1 H-15 N HSQC spectrum.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have demonstrated that Jaburetox and its mutants can form wellresolved, highly cation-selective channels. The peptide corresponding to the N-terminal part of Jaburetox is more active in negative potentials, while the ion-channel activity of Jaburetox and the other mutants do not display voltage dependence [24].…”
Section: Introductionmentioning
confidence: 99%
“…2017 DOI: 10.1590/S0100-204X2017001200016 microorganisms to carbohydrates; and improves digestibility by changing fiber structure (Wanapat et al, 2009;Polyorach & Wanapat, 2015). Soybean (Medeiros-Silva et al, 2014) and jack bean (Piovesan et al, 2014) are common urease sources. Other legumes like pigeon pea, however, also contain this enzyme (Balasubramanian et al, 2013).…”
Section: Introductionmentioning
confidence: 99%